Improved outcome of patients with relapsed/refractory Hodgkin lymphoma with a new fotemustine‐based high‐dose chemotherapy regimen. (12th October 2015) - Musso, Maurizio; Messina, Giuseppe; Di Renzo, Nicola; Di Carlo, Paolo; Vitolo, Umberto; Scalone, Renato; Marcacci, Gianpaolo; Scalzulli, Potito R.; Moscato, Tiziana; Matera, Rossella; Crescimanno, Alessandra; Santarone, Stella; et al.
Summary: High‐dose chemotherapy (HDT) with autologous stem cell transplantation is the standard of care for relapsed/refractory (RR) Hodgkin lymphoma (HL). Given that HDT may cure a sizeable proportion of patients refractory to first salvage, development of newer conditioning regimens remains a priority. We present the results of a novel HDT regimen in which carmustine was substituted by a third‐generation chloroethylnitrosourea, fotemustine, with improved pharmacokinetics and safety (FEAM; fotemustine, etoposide, cytarabine, melphalan) in 122 patients with RR‐HL accrued into a prospective registry‐based study. Application of FEAM resulted in a 2‐year progression‐free survival (PFS) of 73·8% [95% confidence interval (CI), 0·64–0·81] with median PFS, overall survival and time to progression yet to be reached. The 2‐year risk of progression adjusted for the competitive risk of death was 19·4% (95% CI, 0·12–0·27) for the entire patient population. Most previously established independent risk factors, except for fluorodeoxyglucose ( 18 F FDG)‐uptake, were unable to predict for disease progression and survival after FEAM. Although 32% of patients had 18 F FDG‐positrin emission tomography‐positive lesions before HDT, the 2‐year risk of progression adjusted for competitive risk of death was 19·4% (95% CI; 0·12–0·27). No unusual acute toxicities or early/late pulmonary adverse events were registered. FEAM emerges as an ideal HDT regimen for RR‐HL patients typically pre‐exposed to lung‐damaging treatments.